Tracing colonic embryonic transcriptional profiles and their reactivation upon intestinal damage - Fazilaty, Hassan; Brügger, Michael David; Valenta, Tomas; Szczerba, Barbara M; Berkova, Linda; Doumpas, Nikolaos; Hausmann, George; Scharl, Michael; Basler, Konrad (Cell reports, 2021)
We lack a holistic understanding of the genetic programs orchestrating embryonic colon morphogenesis and governing damage response in the adult. A window into these programs is the transcriptomes of the epithelial and mesenchymal cell populations in the colon. Performing unbiased single-cell transcriptomic analyses of the developing mouse colon at different embryonic stages (embryonic day 14.5 [E14.5], E15.5, and E18.5), we capture cellular and molecular profiles of the stages before, during, and after the appearance of crypt structures, as well as in a model of adult colitis. The data suggest most adult lineages are established by E18.5. We find embryonic-specific gene expression profiles and cell populations that reappear in response to tissue damage. Comparison of the datasets from mice and human colitis suggests the processes are conserved. In this study, we provide a comprehensive single-cell atlas of the developing mouse colon and evidence for the reactivation of embryonic genes in disease.
Keywords: colon inflammatory disease; hindgut development; Single-Cell Analysis; modely nemocí na zvířatech; kolon; DSS; embryo savčí; colon development; Mesoderm; vývojová regulace genové exprese; Inflammatory Bowel Diseases; Gene Expression Regulation, Developmental; Colitis; buněčná diferenciace; intestinal development; střevní sliznice; analýza jednotlivých buněk; Embryo, Mammalian; intestinal damage; stanovení celkové genové exprese; single-cell atlas; idiopatické střevní záněty; Gene Expression Profiling; Animals; lidé; Humans; zvířata; Colon; Intestinal Mucosa; myši inbrední C57BL; Disease Models, Animal; myši; colitis; Mice, Inbred C57BL; mezoderm; kolitida; Mice; Cell Differentiation; Single cell RNA sequencing